Motivation and Organizational Climate Associating with Employee Performance: A Case of Sony Technology (Thailand) Co., Ltd. - Chienwattanasook, Krisada; Pamornpathomkul, Santikorn; Pholmamuang, Vijittra (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This study aimed to study 1) employees’ motivation level at Sony Technology (Thailand) Co., Ltd., according to Alderfer’s ERG motivation theory; 2) Organizational climate of Sony Technology (Thailand) Co., Ltd.; 3) employee performance level of Sony Technology (Thailand) Co., Ltd.; and 4) association of motivation and organization climate with employee performance. The samples used in this research were of 390 employees of Sony Technology (Thailand) Co., Ltd. Questionnaires were used a research tool. The study found that employees’ motivation in terms of existence needs had positive association with employee performance in terms of quantity (r = 0.527). This was followed by employees’ motivation in terms of growth needs associating with employee performance in terms of time (r = 0.518). Herein, independent variables in all dimensions were moderately associated with dependent variables. In addition, organizational climate in terms of organizational commitment associated with employee performance in terms of quantity (r= 0.540). This was followed by organizational climate in terms of organizational commitment associating with employee performance in terms of time (r = 0.536). The independent variables were moderately associated with dependent variables Article history : Received 10 January 2019 Revised 10 February 2019 Accepted 14 February 2019 SIMILARITY INDEX = 0.00